Non-allowed Pharmacologically Active Substances in Physical and Sexual Performance Enhancing Products - Pellegrinia, Manuela; Concetta Rotolo, Maria; Paolo Busardò, Francesco; Pacifici, Roberta; Pichini, Simona (Current Neuropharmacology, 2017)
Background: Recently, a large amount of physical and sexual performance enhancing products have started to be freely sold mainly on internet web sites as dietary supplements. However, there a high suspicion that pharmacologically active substance, prohibited in these products, can be present to provide the expected effect. Methods: A simple and rapid systematic toxicological analysis by gas chromatography-mass spectrometry and liquid chromatography-tandem mass spectrometry has been applied after a liquidliquid extraction at acidic, neutral and alkaline pH with chloroform-isopropanol (9:1 v/v). The assays were validated in the range from 10 mg to 250 mg/g products showing a good linearity for the calibration curves (r2 ≥0.99). Mean extraction recoveries of analytes from different products were always higher than 90% and intra-assay and inter-assay precision and accuracy were always better than 15%. Results: The developed method was applied to the analysis of products with a high percentage of sales in websites and smart and sexy shops. In twelve of eighty supplements, anabolic steroids, antiestrogenic drugs, psychoactive substances and sildenafil and analogs were identified and quantified. Conclusion: Eventual health hazards caused by the hidden presence of pharmacologically active substances in physical and sexual performance enhancing products are reported.
Keywords: sildenafil